ANALISIS KOMPETENSI GURU DALAM PELAKSANAAN PEMBELAJARAN K13 PADA TEMA 1 SUBTEMA 3 KELAS IV SDN 181 PEKANBARU - Wiwit Yuninda; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by differences in the implementation of the 2013 Curriculum compared to the previous curriculum. This study aimed to describe teachers’ competence in implementing the 2013 Curriculum (K13) learning on Theme 1 Sub-theme 3 for Grade IV at SDN 181 Pekanbaru. The subject of this study was the teacher of class IVB. The research design used in this study was descriptive qualitative. Data were collected through observation, interviews, and documentation. Data analysis in this study employed the Miles and Huberman data analysis technique, which consisted of data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of educative learning carried out by teachers through initial activities, core activities, and closing activities in one sub-theme of learning over four meetings reached 62% of the predetermined criteria. Based on the category of the multilevel scale, the teacher’s competence in implementing learning was classified in the poor interval.